Climate change and development in Latin America and the Caribbean : overview 2009 - Samaniego, Joseluis, coordinator (UN ECLAC SantiagoCL, 2009)
Stresses the importance of finding mechanisms for appropriately distributing the costs of climate change. Points out that major changes are on the way in the global context in which the countries of Latin America and the Caribbean operate and that steps will have to be taken to ensure that the carbon footprint is factored into trade and future investment decisions.